Internet search engine queries on abortion and miscarriage peak after a query on missing a dose of oral contraceptive - Hochberg, Irit; Yom-Tov, Elad (22nd European Congress of Endocrinology, 2020)
Objective: Oral Contraceptives (OCs) are a unique chronic medication where a slip of memory may be experienced as a threat that could change the life course of a person. Internet search engine queries provide a unique access to concerns and information gaps in a large number of internet users. We sought to quantitate internet search engine queries on missing one or more doses of an OC and subsequent queries on emergency contraception, abortion and miscarriage. We also quantified their rate of reporting a pregnancy timed to the cycle of missing an OC. Study design: We extracted all Bing English-language queries submitted in the US during 2018 mentioning a missed OC, and further queries by the same users on miscarriage, abortion, emergency contraceptives and week of pregnancy and analyzed temporal trends and query frequency in different age groups. Results: We identified 26.395 Bing users in the US who searched Bing on missing OC pills and the subfraction who queried about miscarriage, abortion, emergency contraceptive and week of pregnancy after their initial missed OC query. Users under the age of 30 who asked about forgetting an OC dose were more likely to ask about abortion (× 1.5) and emergency contraception (× 1.7) (P-value = 0.00 006 and 0.00 001, respectively), while at ages 30–34 queries about pregnancy (× 2.1) and miscarriage (× 5.4) were more likely (P-value = 0.000002 and 0.000004, respectively). Conclusion(s): A large number of women ask about missing a dose of OC, either because they have not have received sufficient information from their healthcare providers or because they preferred to obtain information online. Queries about abortion and miscarriage peaking in subsequent days may indicate a common worry of possible pregnancy.